Limestone Facies And Diagenesis On Tondo Formation At Kaisabu Village Bau-Bau City Southeast Sulawesi Province - Muhammad Chaerul; La Ode Ngkoimani; Sofyan Sadri (UIR PRESS, 2017)
This study aims to determine the limestone facies and diagenesis on Tondo Formation. The method used was petrographic method bypolarizing microscope. Based on the physical characteristics and biota contained, the carbonate rocks on tondo formation (Tmtl) can be grouped into two facies, namely: Wackestone and Packestone. The diagenesis process that occurred in Tondo Formation research area is microbial micritization, cementation and neomorphism which indicate that the Tondo Formation has existed on diagenetic environment of marine phreatic, meteoric phreatic and meteoric vadose.